"Uciekałem w samotność" - figury romantycznej samotności w "Pamiętnikach szaleńca Gustava Flauberta" - Śniedziewski, Piotr (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The aim of the article is to analyze the experience of solitude in Memoirs of a Madman (1838), one of the youthful works of Gustave Flaubert, where autobiographical and fictional elements are interspersed. The narrator of Memoirs… is a loner in a threefold sense: social (it is a result of reluctance and even hatred towards society and a consequence of misanthropy and romantic elitism), metaphysical (a man in Memoirs… seemsto be abandoned, vainly seeking rest in God or in any au-delà) and existential (Memoirs… are written by someone who is empty, burned out, unable to creatively engage in life; he is a stranger to himself). The typology seems to be an obvious affirmation of romantic phenomenon.But Flaubert’s youthful work is not imitative: the experience of loneliness has been subjected to a process of disillusion that ruins the romantic myths